Articulações entre ensino e pesquisa em ciências da natureza na formação docente para a prática pedagógica crítica: o olhar dos licenciandos - Silva, Nicole de Castro (Universidade Federal de São Carlos, 2020)
Teachers can turn to what they saw in the classroom in planning and running their classes, running the risk of reproducing oppressive practices that do not make it possible to construct knowledge meaningfully. This research seeks to investigate whether the Freirean aspects present in the Biological Sciences Degree course at UFSCar Sorocaba influence the students' practices by exercising the teaching role, in order to promote the criticity and emancipation of the citizen, according to the Freirean assumptions (AMARAL; BERBEL; FREIRE; LIBÂNEO; MARIANI; SAUL E SILVA; VASCONCELOS; ZÓFILI). For this investigation, we used the bibliographical survey, documentary analysis of the pedagogical political project of the Course and the semi-structured interview. Presenting duality between theory and practice and raising new problems in relation to the application of critical theory in uncritical times.
Articulations between teaching and research in nature sciences in teaching training for critical pedagogical practice: the licensors’ look
Keywords: formação docente; Freire; criticidade; CIENCIAS HUMANAS::EDUCACAO::CURRICULO